Cellular Therapy for Repair of Cardiac Damage after Acute Myocardial Infarction. (19th February 2009) - Cook, Matthew M.; Kollar, Katarina; Brooke, Gary P.; Atkinson, Kerry
Abstract : Cardiovascular diseases, particularly acute myocardial infarction, are the leading causes of death worldwide. Important advances have been made in the secondary treatment for cardiovascular diseases such as heart transplantation and medical and surgical therapies. Although these therapies alleviate symptoms, and may even improve survival, none can reverse the disease process and directly repair the lasting damage. Thus, the cure of cardiovascular diseases remains a major unmet medical need. Recently, cellular therapy has been proposed as a candidate treatment for this. Many stem and progenitor cell populations have each been suggested as a potential basis for such therapy. This review assesses some of the more notable exogenous adult cell candidates and provides insights into the mechanisms by which they may mediate improvement in cardiac function following acute myocardial infarction. Research into the cellular therapy field is of great importance for the further planning of clinical trials for cardiac cellular myoplasty.